Exchange Rate Pass-Through into Import Prices of Croatia - Kurtović, Safet; Šehić - Kršlak, Sabina; Halili, Blerim; Maxhuni, Nehat (Naše gospodarstvo/Our economy, 2018)
The main goal of this paper is to examine the influence of macro factors and the degree of the exchange rate pass-through (ERPT) on aggregate and disaggregate import prices of the industrial sectors in the short- and long-run. The study is based on a model used by Campa and Goldberg (2002) and Campa et al. (2005). The ERPT is determined by applying the single equation and the cointegration approach (autoregressive distributed lag model [ARDL]), vector decomposition, and data over the period from 2002Q1 to 2016Q4. In the long-run, the ERPT is complete for the aggregate import and for the industrial sector beverages and tobacco. In the short-run, the ERPT is incomplete for the aggregate import and for majority of industrial sectors. Further, we have discovered that the degree of the ERPT is higher with heterogeneous products than with homogeneous products. Due to the inaccessibility of data for micro factors, we were not able to determine their effect on import prices. The results of our research can help economic policymakers to create adequate measures in the field of economic policies that will improve the competitiveness of the economy. Finally, this paper identified the effect of the volatility degree of the ERPT on the disaggregate import prices of industrial sectors that has not been sufficiently explored so far.